Integrating automatic program repair into software development - Kurnia, Steven (Nanyang Technological University, 2022)
As more part of human life depends on digital infrastructure, any vulnerabilities that were found become more impactful to the public. Thus, it is becoming more crucial for some common vulnerabilities to be detected and fixed as early as possible before it reaches the public. Although many tools can perform automatic program repair produced by academia, they need to be invoked manually. Therefore, these tools do not see widespread use in the industry. This project aims to introduce a framework for integrating these tools into a code editor so that these tools can detect and fix vulnerabilities as soon as possible. An experiment is also performed to test the effectiveness of the implemented framework. We concluded that the implemented framework is able to reduce the amount of work required by developers to locate and fix bugs.